Implementing a maintainable and secure tenancy model - Niemelä, Niklas (My University, 2023)
Software-as-a-Service is a popular software delivery model that provides subscription-based services for customers. In this thesis, we identify key aspects of implementing a maintainable and secure tenancy model through analyzing research literature and focusing on a case study. We also study whether it is beneficial to change a single-tenant implementation to a multi-tenant implementation in terms of maintainability and security. We research common tenancy models and security issues in SaaS products. Based on these, we set out to analyze a case study product, identifying potential problems in its single-tenant implementation. We then decide on changing said model, and show the process of implementing a new hybrid model. Finally, we present validation methods on measuring the effectiveness of such implementation. We identified data security and isolation, efficiency and performance, administrative manageability, scalability and profitability to be the most important quality aspects to consider when choosing a maintainable and secure tenancy model. We also recognize that it is beneficial to change from a single-tenant implementation to a multi-tenant implementation in terms of these aspects.
Keywords: SaaS, Multitenancy, Maintainability, Security